Seed bio-priming with multifaceted PGPR from underutilized medicinal plants enhances disease resistance and improves yield in rice - S. Raghu; B. Jeevan; Devayani Sarmah; Mathew Baite; C. Anilkumar; Rupak Jena; M. K. Bag; B. S. Satapathy; S. D. Mohapatra (Australasian Plant Pathology, 2026)

Nanostructured lipid carriers incorporated natural product: A promising approach for the managment of psoriasis - Puja B. Pujari; Abhijeet C. Shedmake; Anilkumar J. Shinde; Sachin S. Mali; Prerana S. Husukale; Vijay R Chidrawar; Pooja V Nagime; Pramod B. Patil; Sheeba Shafi; Sudarshan Singh (Next Research, 2026)

Recent physiological, genetic, and management perspectives on lodging resistance in rice - Ranjan Kumar Jena; Baneeta Mishra; Soumya Mohanty; Nalini Kanta Choudhury; Swagatika Das; Darshan Panda; Nitish Kumar Jena; Abinash Mishra; Amrita Sharma; B. N. Devanna; Rameswar Prasad Sah; Awadesh Kumar; et al. (Planta, 2026)

Assessment of bakanae disease response, grain trait associations, and cgSSR based molecular diversity reveal significant variation among rice varieties and breeding lines - Debashis Moharana; Debasis Dash; Anilkumar C; Awadhesh Kumar; Debobrata Dey; Sasmita Behera; Soumya Priyadarsinee Mohanty; C. Mithun; Shyamaranjan Das Mohapatra; Lambodar Behera; Bishnu Charan Marndi; Jeevan B; et al. (Physiological and Molecular Plant Pathology, 2026)

Genome-wide identification of genetic determinants for gall midge resistance in rice using genic markers - Basana Gowda Gadratagi; Lopamudra Mandal; Rameswar Prasad Sah; Anilkumar C.; Guru-Pirasanna-Pandi G.; Naveenkumar B. Patil; Nandini Sahu; Muhammed Azharudheen T. P.; Sasmita Behera; Prakash Chandra Rath; Shyamaranjan Das Mohapatra (Journal of Applied Genetics, 2026)

Decoding the genetic basis of Cnaphalocrocis medinalis (Guenee) resistance in rice landraces using SSR markers and association mapping - Soumya Shephalika Dash; Prasanthi Golive; Prakash Chandra Rath; Hirak Chatterjee; Arup Kumar Mukherjee; Anjan Kumar Nayak; Partha Sarathi Tripathy; Sucharita Mohapatra; Anilkumar C; Shyamaranjan Das Mohapatra (Protoplasma, 2026)

Insights Into the Genetic Diversity and Population Structure of Fusarium spp. Associated With Rice Bakanae Disease in Eastern and North‐Eastern India Using Microsatellite Markers - Raghu Shivappa; Prasanna S. Koti; Mathew S. Baite; B. Jeevan; C. Anilkumar; S. R. Prabhukarthikeyan; U. Keerthana; K. N. Shantha; Manas Kumar Bag; Shyamaranjan Das Mohapatra (New Zealand Journal of Botany, 2026)
Bakanae disease of rice has emerged as a major threat in the rice‐growingregions of Eastern and Northeastern India. Under field conditions, Fusarium species associated with bakanae disease of rice exhibit a significant degree of variability. Characterizing the pathogen and its isolates is crucial for understanding this variability. This study aimed to assess the genetic diversity and virulence patterns among 88 Fusarium isolates, the causal agents of rice bakanae disease, collected from various locations across Eastern and Northeastern regions of India. The isolates showed a significant variation in their morphology and virulence pattern. The genetic variability among isolates was assessed using 19 microsatellite markers, all of which were successfully amplified across the isolates. The observed genetic diversity was significant, as indicated by Shannon's information index for marker alleles. Using the marker allele differences among the isolates, pathogen population was subdivided into two groups. The analysis of molecular variance among two subpopulations demonstrated lower variance among population than within population. These findings suggest that the studied pathogen population comprises genetically distinct strains, ranging from highly virulent to moderately virulent. This study enhances our understanding of the diversity and distribution of Fusarium isolates, providing valuable insights for strategic breeding programs and effective disease management strategies.

Candidate gene–based characterization of loci underlying grain quality and phytic acid in aromatic rice - Sasmita Behera; Rameswar Prasad Sah; Awadhesh Kumar; Khirod Kumar Sahoo; Muhammed Azharudheen TP; Soumya Priyadarshinee Mohanty; Abhishek Kumar Sahu; Anilkumar C; Bishnu Charan Marndi; Debashis Moharana; Sunil Kumar Nair; Namita Singh; et al. (Genetic Resources and Crop Evolution, 2026)

A robust 1K-core marker set for wild germplasm management and targeted pre-breeding of rice: development and applications - Debashree Dalai; Dipti Ranjan Pani; Swayamsiddha Aswita Dhal; Motilal Behera; Tapan Kumar Mondal; Muhammad Azaharudheen TP; Joshitha Vijayan; Deepa Sarkar; Pallavi Ghose; Abhijeet Roy; Kutubuddin A Molla; Anilkumar C; et al. (Theoretical and Applied Genetics, 2026)

Corrigendum to “Soil policy principles and a policymaking framework using the soil security concept” [Environ. Sci. Policy 168 (2025) 104057] - Amin Sharififar; Pasquale Borrelli; Sandra J. Evangelista; Damien Field; Trevan Flyn; Nicolas Francos; Irene Heuser; Anilkumar Hunakunti; Alex McBratney; Budiman Minasny; Fatima Moreira; Cristine L.S. Morgan; et al. (Environmental Science & Policy, 2025)

Soil policy principles and a policymaking framework using the soil security concept - Amin Sharififar; Pasquale Borrelli; Sandra J. Evangelista; Damien Field; Trevan Flynn; Nicolas Francos; Irene Heuser; Anilkumar Hunakunti; Alex McBratney; Budiman Minasny; Fatima Moreira; Cristine L.S. Morgan; et al. (Environmental Science & Policy, 2025)

QTL-Meta-analysis and Candidate Gene(s) for Anaerobic Germination Potential in Rice - Sanchika Snehi; Pawan Kumar Singh; R. Beena; Suneetha Kota; Satish Kumar Sanwal; K. T. Ravi Kiran; C. Anilkumar; Krishnendu Chattopadhyay; Nitish Ranjan Prakash; Rameswar Prasad Sah (Journal of Plant Growth Regulation, 2025)

Editorial Expression of Concern: Edibility and nutrient analysis of Diospyros crumenata Thw. fruit: an additional fruit resource from the Western Ghats, India - Rahul Jose; S. Praveena; C. Anilkumar; P. S. Jothish (Genetic Resources and Crop Evolution, 2025)

Identification of novel QTL for bakanae disease resistance in non-basmati indica rice - Malabika Khan; S. Raghu; Rameswar Prasad Sah; T. P. Muhammed Azharudheen; Debashis Moharana; Sasmita Behera; P. Soumya Mohanty; B. Jeevan; Lambodar Behera; B.C. Marndi; Sanghamitra Samantaray; C. Anilkumar (Cereal Research Communications, 2025)

Unraveling the genetic diversity in selected rice cultivars released in the last 60 years using gene-based yield-related markers - S. P. Mohanty; A. Khan; S. Patra; S. Behera; A. K. Nayak; S. Upadhyaya; D. Moharana; Muhammed Azharudheen T. P.; C. Anilkumar; M. K. Kar; G. Basana Gowda; B. C. Marndi; et al. (Genetic Resources and Crop Evolution, 2025)

Harnessing the power of genomics to develop climate-smart crop varieties: A comprehensive review - K.T. Ravikiran; R. Thribhuvan; C. Anilkumar; Jayanth Kallugudi; N.R. Prakash; Sandeep Adavi B; N.C. Sunitha; Krishnan P. Abhijith (Journal of Environmental Management, 2025)

Edibility and nutrient analysis of Diospyros crumenata Thw. fruit: an additional fruit resource from the Western Ghats, India - Rahul Jose; S. Praveena; C. Anilkumar; P. S. Jothish (Genetic Resources and Crop Evolution, 2024)

Ustilaginoidea virens, an emerging pathogen of rice: the dynamic interplay between the pathogen virulence strategies and host defense - Sunil Kumar Sunani; Prasanna S. Koti; N. C. Sunitha; Manoj Choudhary; B. Jeevan; C. Anilkumar; S. Raghu; Basana Gowda Gadratagi; Manas Kumar Bag; Licon Kumar Acharya; Dama Ram; Bishnu Maya Bashyal; et al. (Planta, 2024)

Deciphering genotype by year interaction for tea mosquito bug incidence (Helopeltis spp.) in Indian cashew (Anacardium occidentale L.) germplasm - E. Eradasappa; K. Vanitha; M. Babli; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

cgSSR marker based trait associations for Sitotroga cerealella (Olivier) resistance in stored paddy rice - Kajal Priyadarshini; Rameswar Prasad Sah; Totan Adak; G Guru Pirasanna Pandi; T.P Mohammad Azharuddin; C. Anilkumar; S.D. Mohapatra; G. Basana Gowda; Naveenkumar B. Patil (Journal of Stored Products Research, 2024)

Integrated approaches for the management of invasive fall armyworm, Spodoptera frugiperda (J. E. Smith) in maize - Gadde Anilkumar; P. LakshmiSoujanya; D. V. Sai Ram Kumar; V. Manoj Kumar; K. R. Yathish; J. C. Sekhar; H. S. Jat (Journal of Plant Diseases and Protection, 2024)

Revisiting population genetics with new genomic resources in dolichos bean (Lablab purpureus L. Sweet): an orphan crop - Vinayak Spoorthi; S. Ramesh; N. C. Sunitha; C. Anilkumar; M. S. Vedashree (Genetic Resources and Crop Evolution, 2024)

Focused identification of germplasm strategy (FIGS): a strategic approach for trait-enhanced pre-breeding - N. C. Sunitha; M. D. Prathibha; R. Thribhuvan; B. M. Lokeshkumar; P. S. Basavaraj; H. C. Lohithaswa; C. Anilkumar (Genetic Resources and Crop Evolution, 2024)

Cross frontal variability in bio-optical characteristics in the Indian sector of the Southern Ocean during an austral summer - Sudarsana Rao Pandi; Sarat C. Tripathy; S.S. Shaju; N. Anilkumar (Regional Studies in Marine Science, 2023)

Interannual variability of surface bio-optical characteristics in the frontal zones of the Indian sector of the Southern Ocean during austral summer - Sudarsana Rao Pandi; Sarat C. Tripathy; S.S. Shaju; P. Minu; Anvita U. Kerkar; C.C. Bajish; N. Anilkumar (Polar Science, 2023)

The Coorg Block, southern India: Insights from felsic and mafic magmatic suites on Mesoarchean plate tectonics and correlation with supercontinent Ur - Cheng-Xue Yang; M. Santosh; Jarred C. Lloyd; Stijn Glorie; Pin Gao; Bing Yu; Y. Anilkumar; K.S. Anoop; Sung-Won Kim (Gondwana Research, 2023)

Sorption behavior studies of Cs and its migration in soil samples around Visakhapatnam, India - Sukanta Maity; P. Sandeep; S. Mishra; C. B. Dusane; D. K. Chaudhary; P. Padma Savitri; J. Sudhakar; Anilkumar S. Pillai; A. Vinod Kumar (Environmental Monitoring and Assessment, 2023)

Mapping genetic determinants for grain physicochemical and nutritional traits in brown and pigmented rice using genome-wide association analysis - Krishnendu Chattopadhyay; Torit Baran Bagchi; Priyadarsini Sanghamitra; Sutapa Sarkar; C. Anilkumar; Bishnu Charan Marndi; Awadhesh Kumar; Nutan Moharana; Shuvendu Shekhar Mohapatra; Soumya Kumar Sahoo (Euphytica, 2023)

Advances in integrated genomic selection for rapid genetic gain in crop improvement: a review - C. Anilkumar; N. C. Sunitha; Harikrishna; Narayana Bhat Devate; S. Ramesh (Planta, 2022)

Unravelling genetic architecture and development of core set from elite rice lines using yield-related candidate gene markers - Rameswar Prasad Sah; Sasmita Behera; Sushant Kumar Dash; T. P. Muhammed Azharudheen; Jitendriya Meher; Awadhesh Kumar; Bishnu Charan Marndi; Meera Kumari Kar; H. N. Subudhi; C. Anilkumar (Physiology and Molecular Biology of Plants, 2022)

Genome-wide association analysis for plant type characters and yield using cgSSR markers in rice (Oryza sativa L.) - T. P. Muhammed Azharudheen; Amrit Kumar Nayak; Sasmita Behera; C. Anilkumar; Bishnu Charan Marndi; Debashis Moharana; Lalan Kumar Singh; Sameer Upadhyay; Rameswar Prasad Sah (Euphytica, 2022)

Assessment of natural DNA methylation variation and its association with economically important traits in dolichos bean (Lablab purpureus L. Var. Lignosus) using AMP-PCR assay - H. Ajaykumar; S. Ramesh; N. C. Sunitha; C. Anilkumar (Journal of Applied Genetics, 2021)

Picturing beach erosion and deposition trends using PSInSAR: an example from the non-barred southern west coast of India - K. S. Sajinkumar; H. S. Bincy; E. H. Bouali; T. Oommen; C. L. Vishnu; Y. Anilkumar; K. P. Thrivikramji; S. Keerthy (Wetlands Ecology and Management, 2021)

Breeding potential of crosses derived from parents differing in fruiting habit traits in chilli (Capsicum annuum L.) - C. Anilkumar; A. Mohan Rao; S. Ramesh (Genetic Resources and Crop Evolution, 2021)

Genetics of fruit yield and its component traits under different fruiting habit backgrounds in chilli (Capsicum annuum L.) - C. Anilkumar; A. Mohan Rao; S. Ramesh; B. Bhavani; Pranesh (Journal of Genetics, 2019)

A porcine-cholecyst-derived scaffold for treating full thickness lacerated skin wounds in dogs - Satheesan Karthika; Sainulabdeen Anoop; C. B. Devanand; M. K. Narayanan; Madhavan Unni; Saji Eassow; Thapasimuthu Anilkumar (Veterinary Research Communications, 2018)

Nitrogen uptake by phytoplankton in surface waters of the Indian sector of Southern Ocean during austral summer - S. C. Tripathy; Sivaji Patra; K. Vishnu Vardhan; A. Sarkar; R. K. Mishra; N. Anilkumar (Frontiers of Earth Science, 2018)

Common and distinct neural effects of risperidone and olanzapine during procedural learning in schizophrenia: a randomised longitudinal fMRI study - Veena Kumari; Ulrich Ettinger; Seoung Eun Lee; Christine Deuschl; Anantha P. Anilkumar; Anne Schmechtig; Philip J. Corr; Dominic H. ffytche; Steven C. R. Williams (Psychopharmacology, 2015)

Biological response to physical processes in the Indian Ocean sector of the Southern Ocean: a case study in the coastal and oceanic waters - N. Anilkumar; Racheal Chacko; P. Sabu; Honey U. K. Pillai; Jenson V. George; C. T. Achuthankutty (Environmental Monitoring and Assessment, 2014)

Gametophytic selection for wilt resistance and its impact on the segregation of wilt resistance alleles in chickpea (Cicer arietinum L.) - R. L. Ravikumar; G. N. Chaitra; Anilkumar M. Choukimath; C. D. Soregaon (Euphytica, 2013)

Fairweather atmospheric electricity at Antarctica during local summer as observed from Indian station, Maitri - C. Panneerselvam; C. Selvaraj; K. Jeeva; K. U. Nair; C. P. Anilkumar; S. Gurubaran (Journal of Earth System Science, 2007)